Making the best of two worlds: rural and peri-urban livelihood options sustained by nontimber forest products from the Bolivian Amazon - Stoian, D. (2005)
Strategies to foster development based on nontimber forest products (NTFPs) implicitly target rural producers. In the northern Bolivian Amazon, however, NTFP-based benefits also accrue to peri-urban populations. A household survey (n = 120) at the periphery of Riberalta, the region’s economic center, reveals that peri-urban livelihoods depend significantly on both the extraction of Brazil nut and palm heart and their urban-based processing. Migrant and educational background are key determinants for the degree of dependence. Valuation of NTFP-based development contributions needs to allow for the rural–urban continuum underlying NTFP extraction and processing, and the role migration plays in related livelihood strategies.